Eettinen tekoäly ja sen raportointi suomalaisissa yrityksissä - Poltinora, Aino (2025)
The practice of corporate responsibility reporting allows businesses to share their activities regarding economic and social and environmental accountability. Through reporting activities organizations achieve transparency goals while building stakeholder trust and support sustainable development efforts. The fast progress of artificial intelligence technology during recent years brought forth new ethical and societal challenges in corporate responsibility domains. Businesses need to demonstrate and disclose their responsible handling of technology to their stakeholders.